DUKUNGAN SOSIAL DAN KEMANDIRIAN ODHA DI WILAYAH KABUPATEN TUBAN - Yasin Wahyurianto; Teresia Retna Puspitadewi; Setyaningsih . (JURNAL PENELITIAN KESEHATAN, 2015)
The strategy to eradicate HIV - AIDS is make people living with HIV productive and beneficial for actualconstruction.The negative stigma In society make them stress which would have an impact negative forhealth. One of intervention through social support by living more independent in daily needs. This researchaims to obtain an overview of social support and independence on living. the research are descriptive usedcrosssectional approach.The subject of this studvls people living with HIV whose living in Tuban, number ofsample was 40. In this research used questionnaire. The results show social support highest ever in theinstrumental which really make an impact on the life of the good living.The aspect of independence seen onaspects of emotion and behavior although being in negative stigma on society. The most important is providepeople living with HIV opportunities for living to realize the idea, appreciate the idea, provides a path tobecome independent.Keywords: Soc/al support, independence, people living WIthHIV people living with HIV